Akkermansia muciniphila Associated with Improved Linear Growth among Young Children, Democratic Republic of the Congo - George, Christine Marie; Birindwa, Alves; Li, Shan; Williams, Camille; Kuhl, Jennifer; Thomas, Elizabeth; François, Ruthly; Presence, Amani Sanvura; Claude, Bisimwa Rusanga Jean; Mirindi, Patrick; Bisimwa, Lucien; Perin, Jamie; et al. (Emerging infectious diseases, 2023)
To investigate the association between enteric pathogens, fecal microbes, and child growth, we conducted a prospective cohort study of 236 children <5 years of age in rural eastern Democratic Republic of the Congo. We analyzed baseline fecal specimens by quantitative PCR and measured child height and weight at baseline and growth at a 6-month follow-up. At baseline, 66% (156/236) of children had >3 pathogens in their feces. We observed larger increases in height-for-age-z-scores from baseline to the 6-month follow-up among children with Akkermansia muciniphila in their feces (coefficient 0.02 [95% CI 0.0001-0.04]; p = 0.04). Children with Cryptosporidium in their feces had larger declines in weight-for-height/length z-scores from baseline to the 6-month follow-up (coefficient -0.03 [95% CI -0.05 to -0.005]; p = 0.02). Our study showed high prevalence of enteric pathogens among this pediatric cohort and suggests A. muciniphila can potentially serve as a probiotic to improve child growth.